Analisis Perkembangan Penduduk Miskin, Karakteristik Kemiskinan dan Kedalaman Kemiskinan di Indonesia - Mansur, Yuwarman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Poverty is a very complex issue that affects all countries in much the same way. Poverty is a socio-economic phenomenon that transcends not only religious boundaries but also ethnic and national boundaries. The main purpose of this study is to conduct a descriptive analysis to clarify the number of poor people in Indonesia, the characteristics of poverty, how the depth of poverty has developed and to what extent, and the impact on the Indonesian economy. It is something to do. The data used in this study is panel data that collects cross-sectional data from all provinces in Indonesia, and the time-series data is from the past five years from 2017 to 2021. The analysis results of the